Zn-Co metal organic frameworks coated with chitosand and Au nanoparticles for chemo-photothermal-targeted combination therapy of liver cancer - Yang, Congling; Tiwari, Santosh K.; Guo, Lianshan; An, Guanghui; Zheng, Heming; Huang, JianFeng; Jiang, Li; Bai, Zhihao; Zhu, Yanqiu; Wang, Nannan (Frontiers in Oncology, 2023)
The toxic effects of chemotherapy drugs on normal tissues are still a major limiting factor in cancer treatment. In this paper, we report a metal-organic framework (Zn-Co ZIF) with chitosan-coated outer layer as a carrier for the drug adriamycin hydrochloride (DOX), a treatment for liver cancer, as a novel anti-cancer nanodrug-enhanced carrier. Gold nanoparticles, a good photothermal conversion agent, were combined with the target SH-RGD during surface functionalisation to prepare Zn-Co ZIF@DOX-CS-Au-RGD (ZD-CAR), a nanoplatform with good photothermal conversion properties and targeting for combined liver cancer therapy. ZD-CAR was developed after RGD accurately targeted the tumour and entered the tumour microenvironment (TME), it cleaves and releases the liver cancer therapeutic agent (DOX) in a weak acidic environment to effectively kill tumour cells. The metal skeleton cleavage releases Co2+, which catalyzes the production of oxygen from H2O2 to alleviate the tumour hypoxic environment. The dissolved oxygen could reach 14 mg/L after adding 80 mg/mL of ZD-CAR. Meanwhile, gold nanoparticles could convert light energy into heat energy under 808 NIR irradiation to induce local superheating and kill tumour cells. In summary, this study developed a nanoplatform that combines chemo-photothermal-targeted therapy. It has shown good therapeutic effeciency in cellular experiments and performance tests and has promising applications in anti-cancer therapy.